The role of thaumatin II in cucumber resistance against Tetranychus urticae Koch: laboratory and greenhouse evaluation - Kiełkiewicz, Małgorzata; Czarnecka, Małgorzata; Orzechowski, Sławomir; Szwacka, Maria (Biological Letters, 2010)
The role of thaumatin II in the resistance of transgenic cucumber plants of the T6 generation against the two-spotted spider mite (TSSM) (Tetranychus urticae C. L. Koch 1836, Acari: Tetranychidae) was determined in greenhouse experiments evaluating: (1) mite behaviour towards cucumber lines (T224 09, T212 01, T210 06) differing in the level of thaumatin II expression, (2) mite reproductive capacity, (3) mite colonisation ability, and (4) mite leaf damage. Additionally, using Western blot, the presence of thaumatin II in leaves of transgenic cucumber plants of the T6 generation was analysed before and after TSSM feeding. Even plants with a relatively high leaf thaumatin II level (T224 09 and T212 01) were equally well accepted by TSSM in a ‘free-choice’ test, which excludes thaumatin II as an important factor in the process of host plant acceptance. However, a reduced fecundity of mite females and a lower, than in the control, number of mites found in the period of permanent feeding on thaumatin-rich plants, indicate a putative role of thaumatin II in the plant-mite interactions. The lack of a clear relationship between the level of thaumatin II and plant resistance to TSSM may be a sign that thaumatin II is not a direct factor involved in antibiosis. In response to TSSM, the thaumatin II content decreases, increases, or remains unchanged in mite-infested leaves, which excludes thaumatin II as being directly involved in induced defence.